Effect of Heating and Cooling of Aluminium-Based Fibre-Metal Laminates on Their Tensile Strength - Boczar, Kamil; Wasłowicz, Karol; Kubit, Andrzej; Chodorowska, Dorota; Fejkiel, Romuald (Advances in Mechanical and Materials Engineering, 2023)
The widespread use of composite materials in the construction of machines encourages to better understand their properties and the impact of various external factors on these properties. Fibre metal laminates (FMLs) consist of alternating layers of metal and a polymer matrix laminate reinforced with continuous fibres. The aim of this work was to investigate the effect of cyclical temperature changes and thermal shocks (heating the sample to a high temperature in a short time) on the strength properties of FMLs from AW-1050A aluminium sheet, glass fibre fabric and carbon fibre fabric. The research concerns the determination of how cyclical temperature changes affect the tensile strengths properties of FMLs. The results indicate a small effect of the cycles on the tensile strength of the composites. The composites with glass fibre reinforced laminate also showed high resistance to delamination, moreover, the samples did not delaminate even after they were broken. The carbon fibre reinforced laminate composites showed a tendency to delaminate after heat treatment.